Chorioretinal Alterations Induced by Preeclampsia - Xinyi He; Yimei Ji; Meiting Yu; Yuhua Tong (Journal of Ophthalmology)
Hypertension during pregnancy, which is essentially a microvascular disease that destroys the end-organ microcirculation, should not be underestimated, as it could lead to organ failure in the kidneys, lungs, and brain. Preassessment of the microcirculatory state through systematic observation of the fundus has been proven to be noninvasive and feasible. Although hypertension in preeclampsia patients will resolve after childbirth, the sticking point is determining the best termination moment. Early diagnosis and treatment can prevent long-term ocular complications and cardiovascular risks for pregnant women in the future. In order to adjust the treatment strategy through more sensitive and precise fundus changes, we comprehensively summarized the common structural changes in the fundus in preeclampsia patients, including changes in the blood vessels, choroid, and retina, as well as the application of quantitative observation for chorioretinal alterations in recent years.